2007
DOI: 10.1176/appi.ajp.164.1.52
|View full text |Cite
|
Sign up to set email alerts
|

Neural Circuitry Engaged During Unsuccessful Motor Inhibition in Pediatric Bipolar Disorder

Abstract: Dickstein, Daniel P.; Tone, Erin; and Pine, Daniel S., "Neural circuitry engaged during unsuccessful motor inhibition in pediatric bipolar disorder" (2007 Objective: Deficits in motor inhibition may contribute to impulsivity and irritability in children with bipolar disorder (BPD). Therefore, studies of the neural circuitry engaged during failed motor inhibition in pediatric BPD may contribute to our understanding of the pathophysiology of the illness. We tested the hypothesis that children with BPD and contro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

13
76
3

Year Published

2007
2007
2016
2016

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 84 publications
(92 citation statements)
references
References 16 publications
13
76
3
Order By: Relevance
“…Accordingly, unsuccessful motor inhibition was associated with decreased striatal fMRI activation in pediatric bipolar disorder. A lack of striatal error signals as demonstrated in our study was suggested to account for these motor regulatory deficits and contribute to impulsivity and irritability (Leibenluft et al, 2007) as observed in bipolar patients. Indeed, elevated measures of state and trait impulsivity have been observed in bipolar manic patients (Swann et al, 2003).…”
Section: Outcomesupporting
confidence: 54%
“…Accordingly, unsuccessful motor inhibition was associated with decreased striatal fMRI activation in pediatric bipolar disorder. A lack of striatal error signals as demonstrated in our study was suggested to account for these motor regulatory deficits and contribute to impulsivity and irritability (Leibenluft et al, 2007) as observed in bipolar patients. Indeed, elevated measures of state and trait impulsivity have been observed in bipolar manic patients (Swann et al, 2003).…”
Section: Outcomesupporting
confidence: 54%
“…While the strength of these studies is the consistency of these main findings, there are inconsistencies regarding the potential effects of psychotropic medication and associated methodological limitations that make it difficult to draw firm conclusions. Some studies find no significant effects of psychotropic medication on functional neuroimaging measures (14)(15)(16)20,24). In many of these studies, however, the small sample sizes inherent in examining individuals taking versus those not taking each individual class of psychotropic medication make it possible that findings of no significant effect of psychotropic medication resulted from type II error, as authors of these studies have emphasized in discussions of their findings (e.g., reference 24).…”
Section: Effects Of Psychotropic Medication On Functional Neuroimaginmentioning
confidence: 99%
“…Functional neuroimaging studies in bipolar adults and adolescents demonstrate abnormally decreased activity in prefrontal cortical regions during cognitive control and abnormally increased activity in subcortical limbic regions during emotion processing that may persist during remission, depression, and mania (14,15,27). More recent studies have examined neural activity in remitted bipolar populations, many of whom were medicated (13,(21)(22)(23).…”
Section: Functional Neuroimaging Studiesmentioning
confidence: 99%
“…For young people with bipolar disorder, increased activation of the striatum has been found in functional MRI studies of cognitive interference [76] and working memory [77], while reduced activation of the striatum was found in a study of unsuccessful motor inhibition [78].…”
Section: Neurobiological Characteristicsmentioning
confidence: 99%